Revolutionizing Construction through Enhanced Project Management and Sustainability with Industry 4.0 Technologies - Fabiha Fatima, Agha; Syed, Saad; Muhammad Tariq, Bashir; Sumayya, Obaid; Ijaz, Ahmad; Munir Hayet, Khan; Muhammad, Bilal (INTI International University, 2024)
With limited resources and a focus on sustainability, building industry staff face increasing pressure to innovate. This research explores best practices in construction to understand how Industry 4.0 technologies (AI, Robotics, AR/VR, Digital Twins) can transform project management. Through a bibliometric study and literature review, it identifies current technology adoption and barriers. The solution is a program for implementing these technologies to streamline operations, reduce waste, and boost participation. Key to unlocking Industry 4.0's benefits lies in addressing challenges in training, investment, and interoperability, supported by our findings.